Functionalized Gold Nanoclusters Promote Stress Response in COS‐7 Cells. Issue 4 (6th April 2023) - Linklater, Denver P.; Le Guével, Xavier; Kosyer, Erim; Rubanov, Sergey; Bryant, Gary; Hanssen, Eric; Baulin, Vladimir A.; Pereiro, Eva; Perera, Palalle G.Tharushi; Wandiyanto, Jason V.; Angulo, Ana; Juodkazis, Saulius; et al.
Abstract : Nanotoxicity Ultrasmall gold nanoclusters (AuNC) show great promise for application in theranostics due to their unique optical and physicochemical properties. The associated nanotoxicology concerns need to be carefully considered because of their high diffusion across the cellular barrier. In article number 2200102, Denver P. Linklater, Elena P. Ivanova, and co‐workers reveal new insights into the role of surface modification of 2 nm AuNC on their toxicity with impact on the metabolism of COS‐7 fibroblast‐like cells.